Impact of Servicescape of Restaurants on Consumer Perceptions - A Study based in Kolkata - Nath, Soma; Riya Agarwal, (Management Journal for Advanced Research, 2022)
The current study examines the relationship between the servicescape of a restaurant and its influence on customers across different restaurant settings. It seeks to study the servicescape cues that impact consumer perception and behavioural intention i.e. consumer responses. A questionnaire survey was performed for the same, among different age groups in Kolkata to gain insights about consumer perception. Results indicate that there is an inextricable link between a restaurant servicescape and consumer satisfaction. Dimensions of a servicescape that consumers perceive important came to fore and also the sensory and emotional responses.